OC-017 TRIM44: from prognosis to therapy in oesophageal adenocarcinoma and breast cancer. (28th May 2012) - Ong, C A J; Shannon, N B; Lao-Sirieix, P; Ross-Innes, C; O'Donovan, M; Rueda, O M; Walker, C E; Noorani, A; Hardwick, R; Caldas, C; Fitzgerald, R C
Abstract : Introduction: The incidence of oesophageal adenocarcinoma (EA) has quadrupled in the last 30 years and outcomes remain poor. Unlike other epithelial cancers, targeted therapies for EA are at an early stage. Using gene expression profiling, we have previously identified TRIM44 as an independent prognostic gene in EA. Methods: The aims of this project were to (1) Explore the mechanism of dysregulation of TRIM44 and association with prognosis. (2) Examine the oncogenic potential of TRIM44 in EA and other epithelial cancers (3) Identify therapeutic options exploiting TRIM44 dysregulation. Results: Analysis of our EA expression microarray data (n=75), an independent matched aCGH and expression microarray of 997 breast cancers (BC) and an online database (Tumourscape n=1932, various epithelial tumours) revealed focal amplification of TRIM44 in 8% of EA, 6% of BC and 4% of epithelial tumours. Amplification in EA was validated using FISH on tissue microarrays (n=164). Expression of TRIM44 was copy number driven in both EA and BC and amplification conferred a poor prognosis in BC (p=0.037). Functional work demonstrated oncogenic addiction to TRIM44 in cell line models harbouring amplifications; siRNA knockdown in HSC39 (amplifications) and JIMT-1 (high expression) decreased proliferation of cells by twofold (p<0.05) and increased subG0 fraction on FACS (2.5-fold, p<0.05). In contrast, knockdown in OE19 (low expression) had no observed effect. Overexpression of TRIM44 in Hela cells using a Tet-inducible system increased proliferation (2.5-fold, p=0.0038) and invasiveness (twofold, p<0.05). Analysis of the microarray data (EA and breast) identified a potential link between TRIM44 and the mTOR pathway, and suggested sirolimus (mTOR inhibitor) as a therapeutic option. Validation of these findings were performed by IHC of amplified EA samples and showed exact co-localisation of TRIM44 and p-mTOR staining. In addition, treatment of HSC39 and JIMT-1 with RAD001 (mTOR inhibitor) showed that they were highly sensitive (IC50 <30 nm). Conclusion: TRIM44 is amplified in >5% of EA leading to increased proliferation and invasion in vitro. Our data suggest a mode of action of TRIM44 via the mTOR pathway. Evaluation of mTOR inhibitors in EA tumours is worthy of consideration and these are currently being evaluated in phase I/II oncology clinical trials in other epithelial cancers such as renal cell and lung cancer). Assessment of TRIM44 amplification status may allow selection of patients who are more likely to respond. Competing interests: None declared.